2021
DOI: 10.3390/polym13213758
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Caffeine Treatment for Wood Protection—Influence of Wood and Fungi Species

Abstract: In the future, we can expect increased requirements to the health and ecological integrity of biocides used for the protection of wood against bio-attacks, and it is therefore necessary to search for and thoroughly test new active substances. Caffeine has been shown to have biocidal efficacy against wood-destroying fungi, moulds and insects. The aim of the research was to determine whether the effectiveness of caffeine, as a fungicide of natural origin, is affected by a different type of treated wood. Norway s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Caffeine is an alkaloid that has recently been extensively researched for its use in wood preservation. Literature reports have indicated that wood treated with a caffeine solution showed resistance to fungal attack, however, the effectiveness of caffeine as a natural fungicide depends on its concentration, the type of impregnated wood, and the fungus strain used [ 39 , 40 , 41 ]. Various wood species impregnated with an aqueous solution of caffeine were resistant against white rot fungus ( T. versicolor ), brown rot fungi ( C. puteana , P. placenta and G. trabeum ), soft rot fungus ( Ch.…”
Section: Plant-derived Antifungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine is an alkaloid that has recently been extensively researched for its use in wood preservation. Literature reports have indicated that wood treated with a caffeine solution showed resistance to fungal attack, however, the effectiveness of caffeine as a natural fungicide depends on its concentration, the type of impregnated wood, and the fungus strain used [ 39 , 40 , 41 ]. Various wood species impregnated with an aqueous solution of caffeine were resistant against white rot fungus ( T. versicolor ), brown rot fungi ( C. puteana , P. placenta and G. trabeum ), soft rot fungus ( Ch.…”
Section: Plant-derived Antifungal Agentsmentioning
confidence: 99%
“…Various wood species impregnated with an aqueous solution of caffeine were resistant against white rot fungus ( T. versicolor ), brown rot fungi ( C. puteana , P. placenta and G. trabeum ), soft rot fungus ( Ch. globosum ), wood-staining fungi ( A. pullulans and S. pythiophila ), and molds ( A. niger , A. terreus , C. herbarum , P. variotii , P. cyclopium , P. funiculosum , P. brevicompactum , P. violacea , and T. viride ) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Kobetičová et al [ 46 ] assessed the effect of non-toxic methylxanthines including caffeine and its metabolites—theobromine and theophylline on the growth of four wood-destroying fungal species ( S. lacrymans , C. puteana , G. sepiarium , and T. versicolor ) in the agar test.…”
Section: Plant-derived Antifungal Agentsmentioning
confidence: 99%
“…The strong and wide antifungal potential of caffeine was confirmed against wood decay fungi (C. puteana, P. placenta, G. trabeum and T. versicolor), wood-staining fungi (A. pullulans and S. pythiophila) and molds (A. niger, A. versicolor, A. terreus, Ch. globosum, C. herbarum, P. variotti, P. cyclopium, P. funiculosum, Phoma violacea, P. brevicompactum and T. viride) (Lekounougou et al 2007;Barbero-López et al 2018;Kwaśniewska-Sip et al 2018, 2019aPánek et al 2021;Šimůnková et al 2021). A significant reduction in fungal resistance of caffeine-treated wood was observed, when the wood samples were subjected to leaching with water according to EN 84 (1997).…”
Section: Decay Resistance Of Treated Woodmentioning
confidence: 99%
“…Caffeine showed resistance against decay wood fungi and molds. Wood impregnated with caffeine solutions was effectively protected against brown rot fungi (C. puteana, Poria placenta and Gloeophyllum trabeum), white rot fungi (Trametes versicolor), wood-staining fungi (Aureobasidium pullulans and Sclerophoma pythiophila) and molds (Aspergillus niger, Aspergillus terreus, Cladosporium herbarum, Penicillium brevicompactum, Penicillium cyclopium, Penicillium funiculosum, Trichoderma viride, Chaetomium globosum and Paecilomyces variotii) (Kwaśniewska-Sip et al 2018;Pánek et al 2021;Šimůnková et al 2021). However, resistance against fungi of caffeine-treated wood decreases when the wood samples were subjected to leaching procedure, which is caused by partially extracted caffeine from the wood structure under the influence of water (Kwaśniewska-Sip et al 2018;Šimůnková et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, methylxanthines feature an interesting antifungal activity, given that they inhibit fungal chitinases that are necessary for fungal cell wall remodeling and cell replication [3]. In fact, several studies have put forward caffeine-and more recently, theophylline-as ecological, safe, and affordable alternatives to conventional biocides for wood protection [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%